1995
DOI: 10.1016/0196-9781(94)00204-j
|View full text |Cite
|
Sign up to set email alerts
|

Endorphin and MSH in concert form the corticotropic principle released by tilapia (Oreochromis mossambicus; Teleostei) melanotropes

Abstract: diacetyl-tt-MSH. Evidence is presented that the noteworthy corticotropic potency of this HPLC fraction, previously attributed to diacetyl-tt-MSH, results from END and MSH acting in a coordinated fashion. Confinement stress had no effect on plasma N-ac-/?-END immunoreactivity, but led to a decrease in plasma or-MSH levels. Therefore, it seems unlikely that the corticotropic action of the peptides regulates the elevation of cortisol production that takes place during confinement, but it may play a role during ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Plasma levels of cortisol are increased in response to stress (see Barton, 1997;. In brown trout (Salmo trutta) and tilapia, plasma levels of α-MSH are also increased by stress (Sumpter et al, 1985;Balm et al, 1995). Plasma cortisol levels in the cannulated trout in this study were essentially similar to the basal levels observed in the previous study (Sumpter et al, 1985), suggesting that intra-arterial injection of the hormones and blood sampling was done under minimum stress.…”
Section: Discussionsupporting
confidence: 77%
“…Plasma levels of cortisol are increased in response to stress (see Barton, 1997;. In brown trout (Salmo trutta) and tilapia, plasma levels of α-MSH are also increased by stress (Sumpter et al, 1985;Balm et al, 1995). Plasma cortisol levels in the cannulated trout in this study were essentially similar to the basal levels observed in the previous study (Sumpter et al, 1985), suggesting that intra-arterial injection of the hormones and blood sampling was done under minimum stress.…”
Section: Discussionsupporting
confidence: 77%
“…In teleosts, -endorphin and -MSH alone or in concert display corticotrophic activity in some species (Lamers et al 1992, Balm et al 1995. Recently, in carp, the presence of a corticotrophic factor in the pituitary PI was confirmed, but this factor was neither -MSH nor -endorphin, alone or in concert (van den Burg et al 2003).…”
Section: Innervation Of the Teleost Pituitary Glandmentioning
confidence: 99%
“…-MSH appears to be a less likely cortisol secretagogue at this stage of development, because the most corticotrophic form (di-acetylated -MSH; Balm et al 1995) was not present in these larvae. In addition to ACTH and -MSH, other neuroendocrine factors, such as acetylcholine and atrial natriuretic peptide (Kloas et al 1994), may be involved because, as in mammals and other teleosts, the control of cortisol release in carp is multifactorial.…”
Section: Functional Development Of the Hpi Axismentioning
confidence: 99%